Granulocyte-Colony-Stimulating Factor Effectively Shortens Recovery Duration in Anti-Thyroid-Drug-Induced Agranulocytosis: A Systematic Review and Meta-Analysis - Wang, Yonghui; Li, Xiaoying; Yang, Qian; Wang, Wei; Zhang, Yanan; Liu, Jun; Zheng, Liang; Zha, Bingbing (Frontiers in Endocrinology, 2019)
Background and aim: Granulocyte-colony-stimulating factor (G-CSF) is highly beneficial as a general treatment for anti-thyroid drug (ATD)-induced agranulocytosis. This meta-analysis aimed to assess the clinical effects of G-CSF and non-G-CSF on recovery duration in patients with ATD-induced agranulocytosis by analyzing the overall clinical outcomes. Methods: PubMed, Embase, Ovid, Cochrane, Google Scholar, China National Knowledge Infrastructure （CNKI ）databases were searched for published studies from 1900 to 2018. No language restriction was implemented. Results: This meta-analysis included 10 published retrospective studies and 1 prospective study. Data were obtained from 11 trials (474 patients: 247 with G-CSF and 227 with non-G-CSF treatment). Compared with the non-G-CSF group, the G-CSF group presented shorter recovery duration [weighted mean difference (WMD) = –3.04 days, 95% confidence interval (95% CI): –4.38 to –1.67 (Z = 4.43 P = 0.000)]. However, the recovery duration fluctuated across different regions and recovery criteria. Asian patients achieved significant clinical outcomes [WMD = –3.16 days (95% CI: –4.58 to –1.74, P = 0.000)] compared with European and South American patients [WMD = –2.19 days (95% CI: –7.38 to 3.01, P = 0.409)]. Also, according to various recovery criteria, the duration of granulocyte count increase of more than 1.5 or 1.0 × 109/L [WMD = –3.50 days (95% CI: –4.82 to –2.18, P = 0.000)] revealed better treatment effect. Conclusion: G-CSF could significantly shorten the recovery duration in patients with ATD-induced agranulocytosis.